Femoral head material loss at the head-neck junction in total hip arthroplasty: the effect of head size, stem material and stem offset. Issue 6 (November 2019) - Valente, Giuseppe; Lanting, Brent; MacDonald, Steven; Teeter, Matthew G; Van Citters, Douglas; Howard, James
Introduction: Material loss at the head-neck junction in total hip arthroplasty may cause adverse clinical symptoms and implant failure. The purpose of this study was to quantitatively examine the effects of head size, stem material and stem offset on material loss of the head-neck taper interface of a single trunnion design in retrieval implants of metal on polyethylene bearing surfaces. Methods: A retrieval study was performed to identify all 28-mm and 32-mm femoral heads from a single implant/taper design implanted for >2 years. This included n = 56 of the 28-mm heads and n = 23 of the 32-mm heads. The 28-mm femoral heads were matched to 32-mm femoral heads based on time in vivo and head length. A coordinate measuring machine was used to determine maximum linear corrosion depth (MLD). Differences in MLD for head diameter, stem material, and stem offset were determined. Results: There were no differences between groups for age, gender, BMI, or implantation time. There was no difference in MLD between 28 mm and 32 mm matched paired head diameters ( p = 0.59). There was also no difference in MLD between titanium or cobalt-chromium stems ( p = 0.79), and regular or high-offset stems ( p = 0.95). Conclusion: There is no statistical difference in femoral head MLD at the head-neck junction in THA between 28-mm and 32-mm matched paired femoral heads, similar or mixed alloy coupled femoral head stem constructs, and regular or high offset stems.